3-BocNH-ABNO-catalyzed aerobic oxidation of alcohol at room temperature and atmospheric pressure. Issue 35 (29th August 2019) - Zhao, Yajing; Li, Yutong; Shen, Zhenlu; Hu, Xinquan; Hu, Baoxiang; Jin, Liqun; Sun, Nan; Li, Meichao
Graphical abstract: Highlights: Oxidation of alcohols into corresponding aldehydes and ketones. 3-BocNH-ABNO and NaNO2 as the catalysts, and oxygen as the oxidant. Good to excellent yields can be obtained. The reactions were performed at room temperature and atmospheric pressure. Transition-metal-free reaction conditions. Abstract: A transition-metal-free catalytic system has been developed for selective transformation of alcohol to aldehydes or ketones. The reactions were performed with 3-( tert -butoxycarbonylamino)-9-azabicyclo[3.3.1]nonane N -oxyl (3-BocNH-ABNO) as the catalyst, NaNO2 as the co-catalyst, molecular oxygen as the terminal oxidant, and AcOH as the solvent under room temperature. This catalytic system exhibited broad functional group tolerance. A series of alcohol substrates, including primary and secondary benzylic alcohols, heteroaromatic analogues, primary and secondary aliphatic alcohols, could be converted into their corresponding aldehydes and ketones in good conversions and selectivities.